Caregiver experiences with transitions from pediatric to adult healthcare for children with complex care needs. (24th February 2022) - MacNeill, Lillian; Doucet, Shelley; Luke, Alison
Abstract: Background: Caring for a youth with complex care needs (CCN) who is transitioning from paediatric to adult healthcare can produce many challenges. For example, caregivers must often manage their youth's care at home, coordinate care and advocate for their youth. Experiences of fragmented and uncoordinated care often result in caregivers feeling ill‐prepared and uncertain about the transition process. The current study explores caregiver experiences with the transition from paediatric to adult healthcare for youth with CCN in a semi‐rural Canadian province. Methods: This study used a cross‐sectional qualitative descriptive design, involving semi‐structured interviews with caregivers of youth with CCN who were preparing for, in the process of, or completed a transition from paediatric to adult healthcare within the province of New Brunswick, Canada. Thematic analysis focused on describing caregiver experiences with the transition from paediatric to adult healthcare. Results: Seventeen caregivers completed interviews for this study. Four key themes emerged relating to caregiver experiences with the transition from paediatric to adult healthcare for these youth: (1) lack of caregiver support, (2) lack of continuity of care, (3) need for collaborative care and (4) difficulty navigating transition . Conclusion: There is a clear need to address the challenges experienced by youth with CCN and their caregivers throughout the transition from paediatric to adult healthcare. An effective transition strategy should involve early and coordinated planning between the paediatric and adult care team; continued communication across the care team throughout the transition process; and coordination among health, education and social services.